Surface decoration by Spirulina polysaccharide enhances the cellular uptake and anticancer efficacy of selenium nanoparticles - Li Y (Dove Medical Press, 2012)
Fang Yang1*, Quanming Tang1,2*, Xueyun Zhong3, Yan Bai1, Tianfeng Chen1, Yibo Zhang1, Yinghua Li1, Wenjie Zheng11Department of Chemistry, Jinan University, Guangzhou, China; 2South China Seas Institute of Oceanology, Chinese Academy of Sciences, Guangzhou, China; 3Department of Pathology, Jinan University, Guangzhou, China*These authors contributed equally to this workAbstract: A simple and solution-phase method for functionalization of selenium nanoparticles (SeNPs) with Spirulina polysaccharides (SPS) has been developed in the present study. The cellular uptake and anticancer activity of SPS-SeNPs were also evaluated. Monodisperse and homogeneous spherical SPS-SeNPs with diameters ranging from 20 nm to 50 nm were achieved under optimized conditions, which were stable in the solution phase for at least 3 months. SPS surface decoration significantly enhanced the cellular uptake and cytotoxicity of SeNPs toward several human cancer cell lines. A375 human melanoma cells were found extremely susceptible to SPS-SeNPs with half maximal (50%) inhibitory concentration value of 7.94 µM. Investigation of the underlying mechanisms revealed that SPS-SeNPs inhibited cancer cell growth through induction of apoptosis, as evidenced by an increase in sub-G1 cell population, deoxyribonucleic acid fragmentation, chromatin condensation, and phosphatidylserine translocation. Results suggest that the strategy to use SPS as a surface decorator could be an effective way to enhance the cellular uptake and anticancer efficacy of nanomaterials. SPS-SeNPs may be a potential candidate for further evaluation as a chemopreventive and chemotherapeutic agent against human cancers.Keywords: selenium nanoparticles, Spirulina polysaccharide, cellular uptake, anticancer, apoptosis